Efficiency wages and negotiated profit-sharing under uncertainty - Matthias Göcke (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
Efficiency wage effects of profit sharing are combined with option values related to stochastic future profit variations. These option effects occur if the workers' profit share is fixed by long-term contracts. The Pareto-improving optimal level of the sharing ratio is calculated for two different scenarios. First, if the firm can unilaterally decide, the expected present value of net profits is maximised. Second, if the sharing ratio is based on bilateral Nash bargaining. Since a larger variation of revenues implies a higher redistribution of future profits, the inclusion of expected variations results in a lower worker's profit ratio in both scenarios.
Keywords: D81; J33; 330